Analysis of the Influence of Exports, Imports, Foreign Direct Investment (FDI) and Unemployment on Economic Growth: A Study in 6 ASEAN Countries - Hestika, Dela; Armelly, Armelly (Formosa Journal of Multidisciplinary Research, 2025)
This study aims to analyze the influence of exports, imports, foreign investment (PMA), and unemployment on economic growth in 6 ASEAN  countries, namely Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam, during the period 2017-2022. The method used in this study secondary and panel data analysis. Regression analysis reveals that export, import, and FDI variables have a significant influence on economic growth, while unemployment does not show a significant influence. This study is expected to provide useful information for the government, investors, and academics regarding the factors that influence economic growth in the ASEAN region.